THEORETICAL FOUNDATIONS OF USING AUDIOVISUAL MATERIALS IN LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the theoretical foundations of using audiovisual materials in language teaching and learning processes. Audiovisual materials are considered one of the most effective instructional tools for enhancing learners’ linguistic competence, motivation, and communicative abilities. The study analyzes key pedagogical theories supporting audiovisual instruction, including cognitive learning theory, dual coding theory, and communicative language teaching. Furthermore, the article explores methodological approaches to integrating audiovisual resources into classroom practice and evaluates their impact on learners’ language skills development. The findings demonstrate that audiovisual materials significantly improve listening comprehension, vocabulary acquisition, pronunciation accuracy, and learner engagement when applied systematically and purposefully in language education.